The Impact of Bank Direct Marketing on Enrollment Intention : Opening Bank Account - Hendrianto, Dedy; Hermawanto, Tunjung; Simanjuntak, Evi (Journal of World Science, 2023)
The aim of this research is to further explore the characteristics of marketers that are appropriate for enhancing trust and significantly influencing customers' purchase intentions. The method used in this study is quantitative. Non-probability sampling was used to select a sample of 233 participants. The data analysis technique employed in this research is Structural Equation Modeling (SEM) Partial Least Squares (PLS). The results of the study indicate that product knowledge, friendliness, and communication skills have a positive impact on perceived trust, which in turn stimulates customers' interest in opening a bank account. This study highlights the crucial role of perceived trust as a mediator in this relationship, providing insights for banking institutions to enhance their marketing strategies. For instance, effective communication with the public regarding recognition, awards, company performance, and empowering credible influencers can be beneficial. Additionally, it is noteworthy that product knowledge emerges as the most influential independent variable in shaping perceived trust. Therefore, organizations are encouraged to enhance their marketers' product knowledge through various means such as training, personal experiences, Q&A forums, mentoring, coaching, and attractive incentives.